PENGARUH PENGGUNAAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VII SMP NEGERI 1 MAUROLE - Yosephina Payu Wao; Maria Mega Silvia Pare; Ainun Jariyah (Jurnal Bionatural, 2025)
Learning media is an important element in classroom learning activities. This research aims to determine the effect of using the Canva application as an interactive learning media in improving the learning outcomes of class VII students at SMP Negeri 1 Maurole in Ende Regency, East Nusa Tenggara. The type of research used is quantitative descriptive research. The design used in this research is one group pre-test post-test pre-experiment design. The population in this study was 110 students consisting of four classes, namely classes VII A, VII B, VII C and VII D. The sample for this research was 26 students from class VII B obtained through a purposive sampling technique. The data obtained from the research sample is in the form of student learning outcomes in cognitive aspects. Data analysis was carried out using the Independent Sample T-test using the SPSS version 20 program. The results of the study showed that there was a significant increase in learning outcomes in the cognitive domain after being treated with learning activities using learning media based on the Canva application as shown by the average pretest score. 35, 7 and the average posttest score is 74.62 and is proven by the results of the Paired Sample T-test, namely a significance level of 0.001 which means effective because <0.05, so it can be concluded that the Canva Application media is an interactive learning media effective in improving student learning outcomes